The Effects of Diet and Exercise on Endogenous Estrogens and Subsequent Breast Cancer Risk in Postmenopausal Women - Wiggs, Alleigh G.; Chandler, Justin K.; Aktas, Aynur; Sumner, Susan J.; Stewart, Delisha A. (Frontiers in Endocrinology, 2021)
Endogenous estrogens have been associated with overall breast cancer risk, particularly for postmenopausal women, and ways to reduce these estrogens have served as a primary means to decrease overall risk. This narrative review of clinical studies details how various nutritional and exercise lifestyle interventions have been used to modify estrogen levels and metabolism to provide a protective impact against breast cancer incidence. We also summarized the evidence supporting the efficacy of interventions, outcomes of interest and identified emerging research themes. A systematic PubMed MEDLINE search identified scholarly articles or reviews published between 2000-2020 that contained either a cohort, cross-sectional, or interventional study design and focused on the relationships between diet and/or exercise and overall levels of different forms of estrogen and breast cancer risk and occurrence. Screening and data extraction was undertaken by two researchers. Data synthesis was narrative due to the heterogeneous nature of studies. A total of 1625 titles/abstracts were screened, 198 full texts reviewed; and 43 met eligibility criteria. Of the 43 studies, 28 were randomized controlled trials, and 15 were observational studies. Overall, studies that incorporated both diet and exercise interventions demonstrated better control of detrimental estrogen forms and levels and thus likely represent the best strategies for preventing breast cancer development for postmenopausal women. Some of the strongest associations included weight loss via diet and diet + exercise interventions, reducing alcohol consumption, and consuming a varied dietary pattern, similar to the Mediterranean diet. More research should be done on the effects of specific nutritional components on endogenous estrogen levels to understand the effect that the components have on their own and in combination within the diet.